Żimmī in Islamic Criminal Law: Analysis of Baḥru al-Mażī by Sheikh Marbawi and Its Implementation in Contemporary Muslim-Majority States - Maulidya Mora Matondang (KURAS Institute, 2025)
This article aims to examine the legal position of non-Muslims ‘żimmī’ as subjects of Islamic criminal law when they voluntarily bring their cases to Islamic judicial institutions. Using a qualitative library research method, the study focuses on the analysis of Sheikh Marbawi’s views as articulated in his book Baḥru al-Mażī. The theoretical framework employed is rooted in Islamic legal theory (fiqh), especially the Shafi'i school of thought, and incorporates the theory of al-Iḥsān (legal competence based on marital status) to interpret Ḥadīṡ-based rulings concerning non-Muslim offenders. The study finds that Sheikh Marbawi considers Islamic courts obliged to adjudicate cases involving żimmī when brought before them, and that such cases must be resolved using Islamic law. This view is supported by Ḥadīṡ evidence and aligns with the classical juristic principle that recognizes the legal subjectivity of non-Muslims under certain conditions. The findings contribute to contemporary Islamic legal discourse by reaffirming the inclusiveness of Islamic criminal jurisprudence, emphasizing the importance of legal pluralism within the framework of Dar al-Islam, and highlighting the scholarly contributions of Southeast Asian ulema such as Sheikh Marbawi.